Media Market as an Example of a Deregulated Market: Historical and Social Analysis of the Local Media - Kinal, Jarosław (European Journal of Sustainable Development, 2019)
The media market consists of: media (media, ie television, radio and printed press, as well as new media in the domain), their recipcom and filter, and so-called. regulators, that is organizations and institutions that control media activities (note: Internet content is not a regulation format). The National Council of Radio Broadcasting and Television controls the content of television broadcasting and analyzing programs as well as receiving and receiving concessions. The Office of Electronic Communications assigns and controls the subject of technical possibilities of broadcasting radio and television programs. Citizens' organizations that oversee media activities. These include industry organizations, e.g. journalistic associations. The media are businesses. To the fact that in their activity they are guided not only by interest, openness or mission, but also by financial profit. There are three basic ways to fund the media. Public media owned by the public is financed from the subscription and advertising. The money from the subscription is spent on the so-called mission, advertising revenue - for other purposes (eg entertainment programs). Commercial media is financed from private capital and advertising. Social media (do not mistake them for social networking sites). Setting up and running a television or radio station for a very expensive investment. The media market 1 is available only to you. To, that the value of the collection program along with its popularity. Therefore, more people watched the video, the more you have to pay for advertising during this broadcast. To make as much money as possible, senders need to care about the attractiveness of the program. To do it in various ways, e.g. to decide to profile the program. Universal programs are suitable for various types of programs: entertainment, educational, information etc. Thematic programs such as: culture, sport or motorization. Keywords: media, labor market, local media, Poland, open market